PENGARUH MINAT MAHASISWA MENJADI GURU DAN PENDAPATAN ORANG TUA TERHADAP MOTIVASI MENGIKUTI PENDIDIKAN PROFESI GURU (PPG) - Sri Melika Daud; Meyko Panigoro; Abdulrahim Maruwae; Roy Hasiru; Maya Novrita Dama (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2026)
ABSTRACT Student motivation to participate in Teacher Professional Education (PPG) is an important aspect of preparing competent and professional prospective teachers. However, research simultaneously examining interest in becoming a teacher as an internal factor and parental income as an external factor influencing motivation to participate in PPG remains limited, particularly among education students. This study aims to analyze the effects of students’ interest in becoming teachers and parental income on motivation to participate in PPG, both partially and simultaneously, among Economics Education students at Universitas Negeri Gorontalo. This study employed a quantitative approach with a correlational survey design. The sample consisted of 66 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination. The results showed that interest in becoming a teacher had a positive and significant effect on motivation to participate in PPG (p = 0.007). Parental income also had a positive and significant effect on motivation to participate in PPG (p < 0.001). Simultaneously, both variables had a significant effect, with F = 130.994 (p < 0.001), and explained 57.7% of the variance in motivation to participate in PPG. These findings highlight the importance of strengthening students’ career orientation toward the teaching profession while expanding economic support and access to professional education funding. ABSTRAK Motivasi mahasiswa mengikuti Pendidikan Profesi Guru (PPG) merupakan aspek penting dalam mempersiapkan calon guru yang profesional dan kompeten. Namun, penelitian yang secara simultan mengkaji minat menjadi guru sebagai faktor internal dan pendapatan orang tua sebagai faktor eksternal yang memengaruhi motivasi mengikuti PPG masih terbatas, khususnya pada mahasiswa kependidikan. Penelitian ini bertujuan menganalisis pengaruh minat mahasiswa menjadi guru dan pendapatan orang tua terhadap motivasi mengikuti PPG, baik secara parsial maupun simultan, pada mahasiswa Jurusan Pendidikan Ekonomi Universitas Negeri Gorontalo. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei korelasional. Sampel penelitian berjumlah 66 responden yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan regresi linear berganda, uji t, uji F, serta koefisien determinasi. Hasil penelitian menunjukkan bahwa minat menjadi guru berpengaruh positif dan signifikan terhadap motivasi mengikuti PPG (p = 0,007). Pendapatan orang tua juga berpengaruh positif dan signifikan terhadap motivasi mengikuti PPG (p < 0,001). Secara simultan, kedua variabel berpengaruh signifikan dengan nilai F = 130,994 (p < 0,001) dan mampu menjelaskan 57,7% variasi motivasi mengikuti PPG. Temuan ini menegaskan pentingnya penguatan orientasi karier keguruan sekaligus perluasan dukungan ekonomi dan akses pembiayaan pendidikan profesi.